2017
DOI: 10.1007/s12288-017-0836-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of Soluble Transferrin Receptors and sTfR/log Ferritin in the Diagnosis of Iron Deficiency Accompanied by Acute Infection

Abstract: There are many causes of anemia; the most common of these are acute and chronic infections, iron deficiency, or both. Identifying the cause is a very important step in management of anemia. So, we evaluated the usefulness of soluble transferrin receptor (sTfR) and of the sTfR/log ferritin in the diagnosis of iron deficiency anemia accompanied by acute infection. This study was conducted on 131 children aged 2-11 years old from those who attended the pediatric outpatient clinics in Menoufia university hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Diabetes and AIDS also increase susceptibility to tuberculosis. 37 , 38 The prevalence of PTB in diabetic patients with poor glycemic control was significantly higher than that in patients with good glycemic control. 39…”
Section: Discussionmentioning
confidence: 95%
“…Diabetes and AIDS also increase susceptibility to tuberculosis. 37 , 38 The prevalence of PTB in diabetic patients with poor glycemic control was significantly higher than that in patients with good glycemic control. 39…”
Section: Discussionmentioning
confidence: 95%
“…In rats with iron deficiency anemia, hemoglobin level and serum iron were lower, while TIBC was higher than normal rats (42). A reduction in the percentage transferrin saturation and ferritin together with an increase in soluble transferrin receptors indicate a state of iron deficiency anemia (43,44). Also, it was reported that elevated sTfR/ log ferritin is an efficient index of iron deficiency anemia whether the subject suffers from inflammation or not (44).…”
Section: Discussionmentioning
confidence: 99%
“…When IDA occurs, erythroferrone, a hormone produced by bone marrow erythroblasts, increased and acts on hepatocytes to suppress hepcidin production and thereby increases dietary iron absorption and mobilization from stores [32,33]. It was reported that sTfR were significantly higher than normal in children with IDA [34] and the increase is proportional to tissue iron deficit. The sTfR are sensitive, early and highly quantitative marker of iron depletion.…”
Section: Sequencesmentioning
confidence: 99%